Impact of Carcinogenic Chromium on the Cellular Response to Proteotoxic Stress - Ferreira, Leonardo M. R. (2019)
Worldwide, several million workers are employed in the various chromium (Cr) industries. These workers may suffer from a variety of adverse health effects produced by dusts, mists and fumes containing Cr in the hexavalent oxidation state, Cr(VI). Of major importance, occupational exposure to Cr(VI) compounds has been firmly associated with the development of lung cancer. Counterintuitively, Cr(VI) is mostly unreactive towards most biomolecules, including nucleic acids. However, its intracellular reduction produces several species that react extensively with biomolecules. The diversity and chemical versatility of these species add great complexity to the study of the molecular mechanisms underlying Cr(VI) toxicity and carcinogenicity. As a consequence, these mechanisms are still poorly understood, in spite of intensive research efforts. Here, we discuss the impact of Cr(VI) on the stress response-an intricate cellular system against proteotoxic stress which is increasingly viewed as playing a critical role in carcinogenesis. This discussion is preceded by information regarding applications, chemical properties and adverse health effects of Cr(VI). A summary of our current understanding of cancer initiation, promotion and progression is also provided, followed by a brief description of the stress response and its links to cancer and by an overview of potential molecular mechanisms of Cr(VI) carcinogenicity.